Bremer Kunstpreis 1985. - Kunsthalle, Bremen (Bremen : Kunstverein in Bremen, 1985)
Christian, Abraham David ; Disler, Martin ; Hien, Albert ; Kuckei, Peter ; Meuser ; Münch, Horst ; Prangenberg, Norbert ; Radermacher, Norbert ; von Wedel, Monika
Bremer Kunstpreis 1985, Kunsthalle Bremen, 29. September bis 3. November 1985
boek